2011
DOI: 10.1258/phleb.2010.010016
|View full text |Cite
|
Sign up to set email alerts
|

Pain perception during and after VNUS ClosureFAST™ procedure

Abstract: The objective of the study was first to quantify the level of pain that patients experience during VNUS ClosureFAST™ and in the first week following treatment. Secondly, to investigate the use of pain medication. Thirdly, to identify after how many days patients return to daily activities and whether pain is a factor of influence. A prospective descriptive cohort study was carried out. In all, 104 consecutive VNUS ClosureFAST procedures for greater saphenous vein (GSV) incompetence between 18 May and 28 August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
1
13
0
3
Order By: Relevance
“…reported an average pain score of 2.0, one day after a VNUS Closure FAST ™ ablation of the GSV without phlebectomy with the accompanying use of an average of 300 ml of tumescent solution. Furthermore, 24% of patients required a low dose of paracetamol for 1–3 days post‐intervention . Contrary to other reports, in which each patient was advised to take a nonsteroidal anti‐inflammatory drug for one week post‐endoluminal thermal treatment, we advised patients to take painkillers only when experiencing actual pain .…”
Section: Discussionmentioning
confidence: 93%
“…reported an average pain score of 2.0, one day after a VNUS Closure FAST ™ ablation of the GSV without phlebectomy with the accompanying use of an average of 300 ml of tumescent solution. Furthermore, 24% of patients required a low dose of paracetamol for 1–3 days post‐intervention . Contrary to other reports, in which each patient was advised to take a nonsteroidal anti‐inflammatory drug for one week post‐endoluminal thermal treatment, we advised patients to take painkillers only when experiencing actual pain .…”
Section: Discussionmentioning
confidence: 93%
“…In a study, Ross et al 18 used lidocaine for the local anesthesia. The authors reported that the mean pain score (VAS: 0-10) was 2 in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 104 patients, 45% returned to normal activity on the first postoperative day, with 100% at 1 week 20. Other studies have reported the number of days unable to work after the procedure to be 1 day, with a range of 0–28 days 17,18,21…”
Section: Findings From Literature Searchmentioning
confidence: 98%
“…In studies done under local anesthesia, Closure Fast™ produced average pain scores of between 3 and 4 out of 10 on a visual analog scale during the procedure (from the injection of tumescence). The average postoperative pain scores were less than 2 in the first week, with up to 76% of patients not requiring analgesia and those that did taking only paracetamol and simple non-steroidal anti-inflammatory drugs 18,20,21. The 46 patients in the RECOVERY study had pain scores of less than 1 at 48 hours reducing still further over the first week 22…”
Section: Findings From Literature Searchmentioning
confidence: 99%